Preparation and characterization of sol-gel hybrid coating films for covalent immobilization of lipase enzyme - OGAN, AYŞE; KAHRAMAN, MEMET VEZİR; DEMİR, SERAP (ELSEVIER, 2016)
In this study UV-curable hybrid epoxy-silica polymer films were prepared via sol-gel method. Lipase (EC 3.1.1.3) from Candida rugosa was covalently immobilized onto hybrid epoxy-silica polymer films and immobilization capacity of polymer films was found 7.22 mg g(-1). The morphology of the polymeric support was characterized by scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Immobilized and free enzymes were used in two different reaction systems: hydrolysis of p-nitrophenyl palmitate in aqueous medium and synthesis of p-nitrophenyl linoleate (from p-nitrophenol and linoleic acid) in n-hexane medium. The effect of temperature on hydrolytic and synthetic activities was investigated and observed maximum activities at 50 degrees C and 45 degrees C for immobilized enzyme, orderly. Km values for free enzyme were determined 0.71 and 1.12 mM by hydrolytic and synthetic activity assays, respectively, while these values were observed as 0.91 mM and 1.19 mM for immobilized enzyme. At the end of 30 repeated cycles, 56% and 59% of initial activities remained for hydrolytic and synthetic assays, respectively. Native enzyme lost its activity completely within 20 days, whereas the immobilized enzyme retained for hydrolytic and synthetic activities was approximately 82% and 72%, respectively, under the same storage time. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Lipase; Immobilization; Sol-gel; Hydrolytic activity; Synthetic activity; CANDIDA-RUGOSA LIPASE; NANOFIBROUS MEMBRANES; ADSORPTION; CHITOSAN; SILICA; AMYLASE; BEADS